2020
DOI: 10.1371/journal.pone.0239004
|View full text |Cite
|
Sign up to set email alerts
|

Trying again (and again): Weight cycling and depressive symptoms in U.S. adults

Abstract: As the prevalence of overweight and obesity have risen over the past few decades, so have weight control attempts. Research has shown, however, that intentional weight loss results are often short-lived, with people regaining the weight over time. This can lead to weight cycling-losing and gaining weight repeatedly. Previous research, mostly done over two decades ago, concluded there was no relationship between weight cycling and psychological health. The goal of the current paper was to reexamine the relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…Nevertheless, we have decided to leave these factors in a separate category (because their categorization may not be as immediately clear-cut as others), and these factors include: low-level light [ 429 ], weight cycling [ 430 ], water contaminants [ 431 ], trade [ 432 ], air pollution [ 433 , 434 ], program-level variables (ex. feedback and learning experience) [ 435 ], TV viewing [ 436 ], falls [ 437 ], various other biological factors [ 116 , 136 , 141 , 151 , 164 , 182 , 363 , 364 , 438 , 439 , 440 , 441 , 442 , 443 , 444 , 445 , 446 , 447 , 448 , 449 , 450 , 451 , 452 , 453 , 454 , 455 , 456 , 457 , 458 , 459 , 460 , 461 , 462 , 463 , 464 , 465 , 466 , 467 , 468 , …”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we have decided to leave these factors in a separate category (because their categorization may not be as immediately clear-cut as others), and these factors include: low-level light [ 429 ], weight cycling [ 430 ], water contaminants [ 431 ], trade [ 432 ], air pollution [ 433 , 434 ], program-level variables (ex. feedback and learning experience) [ 435 ], TV viewing [ 436 ], falls [ 437 ], various other biological factors [ 116 , 136 , 141 , 151 , 164 , 182 , 363 , 364 , 438 , 439 , 440 , 441 , 442 , 443 , 444 , 445 , 446 , 447 , 448 , 449 , 450 , 451 , 452 , 453 , 454 , 455 , 456 , 457 , 458 , 459 , 460 , 461 , 462 , 463 , 464 , 465 , 466 , 467 , 468 , …”
Section: Resultsmentioning
confidence: 99%
“…Weight cycling can have negative psychological and behavioral implications with a greater risk for psychopathology [51]. For example, Quinn et al (2020) showed that greater weight cycling is related to depressive symptoms, with stigma as a partial mediator, even after controlling for age, gender, education, income and body mass index [52]. Experimental studies point out that weight cycling causes pronounced stress on the metabolic system, with distinct fluctuations in blood pressure, heart rate, sympathetic activity and levels of lipids, glucose and insulin [53].…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that depression and obesity co-occur to a high degree [ 5 , 6 , 51 , 52 , 53 , 54 ], however the relationship between the two disorders is complex and currently of ambiguous directionality. Stunkard et al presented a summary on the existing data using a moderator/mediator framework in which they classified eating and physical activity as an important mediator of obesity and comorbid depression [ 16 ].…”
Section: Discussionmentioning
confidence: 99%